ON MUSLIM VOTING FOR NON-MUSLIM LEADERS - Makrum Makrum (IAIN Tulungagung, 2019)
This paper examines the Quranic perspective on Muslim voting for non-Muslim candidate leader in the election. It discusses the position of non-Muslim in a majority Muslim and democratic Indonesia and serves as a response to contemporary political rallies against the candidacy of non-Muslim. The Jakarta Governor election in 2017 clearly demonstrated how Muslim politics define non-Muslim in democracy. Examining important concepts on leadership, mainly the doctrine of khalifah, uli al-amr, imam, and awliya’, explained in the Qur’an, this article further argues that this holy scripture has defined criteria of leader for the Muslim. Faith and competencies of leadership candidate serve as main references when Muslim send their vote in the election. In political affairs or nashb al-imamah, Muslim is supposed to vote for Muslim candidate while also having obligation to guarantee the fulfillment of civic rights, particularly for non-Muslim.